2018
DOI: 10.3389/fncel.2018.00372
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Connexin 43 Hemichannels Alleviates Cerebral Ischemia/Reperfusion Injury via the TLR4 Signaling Pathway

Abstract: Connexin 43 (Cx43) widely exists in all components of the neurovascular unit (NVU) and is a constituent of gap junctions and hemichannels. In physiological states, gap junctions are open for regular intercellular communication, and the hemichannels present low open probability in astrocytes. After cerebral ischemia, a large number of hemichannels are unusually opened, leading to cell swelling and even death. Most known hemichannel blockers also inhibit gap junctions and sequentially obstruct normal electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 79 publications
4
36
0
Order By: Relevance
“…However,Gap19 decreased the protein level but not the transcriptional activity of astrocytic Cx43 compared with that in the hemin group. Thus, Gap19 may affect the stability of Cx43 in astrocytes after ICH injury, which is in agreement with the effects of Gap19 on cerebral ischemia injury observed in our prior study [11].…”
Section: Gap19 Reduces Astrocyte Activation and Astrocytic Proin Ammasupporting
confidence: 91%
See 3 more Smart Citations
“…However,Gap19 decreased the protein level but not the transcriptional activity of astrocytic Cx43 compared with that in the hemin group. Thus, Gap19 may affect the stability of Cx43 in astrocytes after ICH injury, which is in agreement with the effects of Gap19 on cerebral ischemia injury observed in our prior study [11].…”
Section: Gap19 Reduces Astrocyte Activation and Astrocytic Proin Ammasupporting
confidence: 91%
“…Our data showed that TAT-Gap19 treatment did not in uence mouse neurobehavioral function under physiological conditions (P>0.05, Figure G-J), which is consistent with our previous studies [11,12]. The mNSSs of the mice were signi cantly increased by ICH damage, while TAT-Gap19 treatment markedly reduced mNSSs (11.20 ± 1.30 vs 6.50 ± 1.29, P<0.01, Figure 2G).…”
Section: Gap19 Improves Neurological Dysfunction After Ich Injurysupporting
confidence: 91%
See 2 more Smart Citations
“…Cells were treated with LPS (1 µg/mL) and different concentrations (10, 30, 50, 100, and 150 mM) of meisoindigo at the beginning of OGD. The optimal dose of LPS was selected based on previous studies (Chen et al, 2018). Then the medium was removed, 10 µl of CCK-8 solution was subsequently added to each well.…”
Section: Drug Treatment and Cell Viability Assay In Vitromentioning
confidence: 99%